Inter-limb differences in upper quarter mobility/stability are not associated with performance in competitive swimmers - Borgmann, Katharina; Panzer, Stefan; Limpach, Sam; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2024)
The Y Balance Test-Upper Quarter (YBT-UQ) is a cost-effective, wellestablished, closed kinetic chain test to assess inter-limb asymmetries in the upper quarter that could negatively affect swimming performance. Thus, the aim of the present study was to determine YBT-UQ performances and inter-limb differences as well as its association with swimming performance in athletes with diverging levels of expertise.Methods: Forty female and male competitive swimmers (age range: 10-22 years) with different expertise levels (A-squad: n=9, B-squad: n=12, C-squad: n=19) were tested (reach distances for the YBT-UQ) and swimming performance was calculated using the ratio of individual to world best time.Results: YBT-UQ performances (i.e., inferolateral reach direction for the dominant arm: p=.027, ηp2=.12 and the non-dominant arm: p=.031, ηp2=.17) but not YBT-UQ inter-limb differences significantly differed between groups and were largest in swimmers with the lowest expertise level (i.e., C-squad). Further, YBT-UQ performances (i.e., inferolateral reach direction [r=-.68 to -.70, both p<.05] and composite score [r=-.65 to -.67, both p<.05] for both arms and medial reach direction for the non-dominant arm [r=-.64, p<.05]) but not inter-limb differences were significantly and negatively correlated with swimming performance among B-squad swimmers.Our results suggest that inter-limb differences in upper quarter mobility/stability are not influenced by the level of expertise and have no significant associations with swimming performance. However, greater reach distances were correlated with lower swimming performance for the B-squad swimmers indicating that a training-related increase in upper quarter mobility/stability could worsen swimming performance in those athletes.